Characteristics of vortex formation and thrust performance in drag-based paddling propulsion - Kim, D.; Gharib, M. (The Journal of Experimental Biology, 2011)
Several characteristics of drag-based paddling propulsion are studied with a simple mechanical model and a measurement technique for mapping three-dimensional flow fields. In drag-based propulsion, the temporal change of the vortex strength is an important parameter in the relationship between vortex formation and thrust generation. Our results indicate that spanwise flow behind the paddling propulsor significantly affects tip vortex development and thrust generation. The distribution of spanwise flow is dependent on the propulsor shape and the Reynolds number. A delta-shaped propulsor generates strong spanwise flow compared with a rectangular propulsor. For the low Reynolds number case, spanwise flow is not as strong as that for the high Reynolds number case. Without sacrificing total impulse, the flexible propulsor can smooth out thrust peaks during sudden stroke motions, which is favorable for avoiding structural failures and stabilizing body motion. We also explored the role of stopping vortex shedding in efficient thrust generation by determining the relationship between stroke angles and total impulses generated by paddling propulsors.